2011
DOI: 10.1152/ajpheart.00216.2011
|View full text |Cite
|
Sign up to set email alerts
|

LEOPARD-type SHP2 mutant Gln510Glu attenuates cardiomyocyte differentiation and promotes cardiac hypertrophy via dysregulation of Akt/GSK-3β/β-catenin signaling

Abstract: LEOPARD syndrome (LS) is an autosomal dominant inherited multisystemic disorder. Most cases involve mutations in the PTPN11 gene, which encodes the protein tyrosine phosphatase Src homology 2-containing protein phosphatase 2 (SHP2). LS frequently causes severe hypertrophic cardiomyopathy (HCM), even from the fetal period. However, the molecular pathogenesis has not been clearly elucidated. Here, we analyzed the roles of the LS-type SHP2 mutant Gln510Glu (Q510E), which showed the most severe type of HCM in LS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 32 publications
5
16
0
Order By: Relevance
“…Importantly, our novel findings demonstrate that pharmacological inhibition of particular signaling steps upstream of mTOR could become feasible therapeutic approaches in the clinical arena. Our results complement the recent findings of two other groups showing that inhibition of phosphoinositide 3 kinase with LY294002 or wortmannin is also effective against the prohypertrophic effects of LS mutations in Shp2 (8,9). This is not surprising because PI3K is an important activator of Akt and, in turn, is regulated by FAK (28,29).…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, our novel findings demonstrate that pharmacological inhibition of particular signaling steps upstream of mTOR could become feasible therapeutic approaches in the clinical arena. Our results complement the recent findings of two other groups showing that inhibition of phosphoinositide 3 kinase with LY294002 or wortmannin is also effective against the prohypertrophic effects of LS mutations in Shp2 (8,9). This is not surprising because PI3K is an important activator of Akt and, in turn, is regulated by FAK (28,29).…”
Section: Discussionsupporting
confidence: 91%
“…Hyperactivation of AKT signaling in response to LS-Shp2 is responsible for HCM in mouse hearts (Ishida et al, 2011;Marin et al, 2011;Schramm et al, 2012). We also observed elevated pAkt levels in response to LS-Shp2 in zebrafish embryos (supplementary material Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Using various in vitro and in vivo models, we and others (8,17,30,43) have previously found that NSML mutations in SHP2 result in increased stimulation of Akt and mammalian target of rapamycin. This leads to enhanced growth signaling and thereby cardiomyocyte hypertrophy.…”
mentioning
confidence: 94%